BEBERAPA CATATAN TENTANG BAHASA PEREMPUAN: PERSPEKTIF WACANA KRITIS - Santoso, Anang (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
It is already generally assumed that women possess characteristicsdistinguishing them from men. One of these characteristics is in their languageuse. Women's language is considered different from men's. In this context, theterm sexist appears. Sexist language represents women and men differently. Suchlanguage also represents women's and men's stereotypes, which is sometimesharmful to both sexes but is more often harmful to women only. Understandingwomen's language involves at least four perspective. First, women's language isperceived as a system of representation, meaning that it is a method of stating orverbalizing a certain event, experience, view, and reality in life. Second, women'slanguage is perceived as a site for social struggle containing a variety of women'sideologies. Third, women's language is perceived as showing women's corneredposition. Fourth, women's language is perceived as showing a relation betweenlanguage and gender where there is asymmetry in language representationbetween men and women.Keywords : women's language, representation, theory of domination, theory ofdifference, gender analysis